Medicinal Mushroom Biotechnology (Global Journal of Science Frontier Research, 2024)
Since most of medicinal mushrooms are rare in nature production of fungal fruiting bodies using artificial cultivation in a form of farming has been intensively established during the last 40 years. Solid state cultivation of various medicinal mushroom mycelia in various types of bioreactors, suitable for veterinary use, appears slightly in last few decades. Developing submerged technologies, using stirred tank and air lift bioreactors, are the most promising technologies for fast and large cultivation of medicinal pharmaceutically active products for human need. This potential initiates the development of new drugs and some of the most attractive over the counter human and veterinary remedies. This article is an overview of the engineering achievements in comprehensive medicinal mushroom mycelia cultivation.
Keywords: medicinal mushrooms; cultivation techniques; bioreactors